Trichoplein binds PCM1 and controls endothelial cell function by regulating autophagy. (26th April 2020) - Martello, Andrea; Lauriola, Angela; Mellis, David; Parish, Elisa; Dawson, John C; Imrie, Lisa; Vidmar, Martina; Gammoh, Noor; Mitić, Tijana; Brittan, Mairi; Mills, Nicholas L; Carragher, Neil O; et al.
Abstract: Autophagy is an essential cellular quality control process that has emerged as a critical one for vascular homeostasis. Here, we show that trichoplein (TCHP) links autophagy with endothelial cell (EC) function. TCHP localizes to centriolar satellites, where it binds and stabilizes PCM1. Loss of TCHP leads to delocalization and proteasome‐dependent degradation of PCM1, further resulting in degradation of PCM1's binding partner GABARAP. Autophagic flux under basal conditions is impaired in THCP‐depleted ECs, and SQSTM1/p62 (p62) accumulates. We further show that TCHP promotes autophagosome maturation and efficient clearance of p62 within lysosomes, without affecting their degradative capacity. Reduced TCHP and high p62 levels are detected in primary ECs from patients with coronary artery disease. This phenotype correlates with impaired EC function and can be ameliorated by NF‐κB inhibition. Moreover, Tchp knock‐out mice accumulate of p62 in the heart and cardiac vessels correlating with reduced cardiac vascularization. Taken together, our data reveal that TCHP regulates endothelial cell function via an autophagy‐mediated mechanism. Synopsis: The interaction of TCHP with PCM1 regulates basal autophagy through controlling GABARAP stability. Loss of TCHP function results in impaired autophagy, the accumulation of SQSTM1/p62 and endothelial dysfunction. TCHP localizes to centriolar satellites, where it binds and stabilizes PCM1. Loss of TCHP results in degradation of PCM1's binding partner GABARAP and impairment of autophagic flux. TCHP regulates endothelial cell function via an autophagy‐mediated mechanism. Abstract : The interaction of TCHP with PCM1 regulates basal autophagy through controlling GABARAP stability. Loss of TCHP function results in impaired autophagy, the accumulation of SQSTM1/p62 and endothelial dysfunction.